2013
DOI: 10.1016/j.ssci.2012.11.001
|View full text |Cite
|
Sign up to set email alerts
|

A clustering regression approach: A comprehensive injury severity analysis of pedestrian–vehicle crashes in New York, US and Montreal, Canada

Abstract: Understanding the underlying relationship between pedestrian injury severity outcomes and factors leading to more severe injuries is very important in dealing with the problem of pedestrian safety. To investigate injury severity outcomes, many previous works relied on statistical regression models. There has also been some interest for data mining techniques, in particular for clustering techniques which segment the data into more homogeneous subsets. This research combines these two approaches (data mining an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
124
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 237 publications
(138 citation statements)
references
References 18 publications
13
124
1
Order By: Relevance
“…Second, based on the variable importance index which identifies the relative importance of each contributed variable in the clustering stage, the following variables were regarded as the most relative factors in accidents: type of region, type of collision, weather condition, road geometric characteristics, road surface condition, and road defects. This is in line with the findings of Xu C et al [11] study, and in total contrast to Mohamed MG et al [13] where none of the foregoing variables were mentioned as effective factors in accident.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Second, based on the variable importance index which identifies the relative importance of each contributed variable in the clustering stage, the following variables were regarded as the most relative factors in accidents: type of region, type of collision, weather condition, road geometric characteristics, road surface condition, and road defects. This is in line with the findings of Xu C et al [11] study, and in total contrast to Mohamed MG et al [13] where none of the foregoing variables were mentioned as effective factors in accident.…”
Section: Discussionsupporting
confidence: 91%
“…In Iran, as in most countries, the legal age to have could be used to help authorities identify effectively the areas with high accident risks, and serve as reference for town planners as far as road safety is considered. Authors of study [13] combined data mining and statistical regression methods to identify the main factors associated with the levels of pedestrian injury. Based on their research, it was found that pedestrian age, location type, driver age, vehicle type, driver alcohol involvement, lighting conditions, and several built environment characteristics influence the likelihood of fatal crashes.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The first step was to identify hotspots of pedestrian crashes using the NKDE implemented in SANET for ArcGIS 10.1 (Okabe, Okunuki, & Shiode, 2006;Okabe et al, 2009) followed by a built-environment audit. Hotspots of pedestrian crashes allow one to target specific areas for further investigation (Mohamed, Saunier, Miranda-Moreno, & Ukkusuri, 2013;Yamada & Thill, 2010). The NKDE used the equal-split continuous kernel method because it is unbiased (Okabe et al, 2009).…”
Section: Methodsmentioning
confidence: 99%
“…The significant variables included roadway width, vehicle type, alcohol involvement, and pedestrian age. Using the same approach, Mohamed et al (2013) used two pedestrian injury severity datasets from New York City, U.S. (2002)(2003)(2004)(2005)(2006) and Montreal, Canada (2003-2006 and applied the ordered probit and multinomial logit models to analyze severity of pedestrian crashes. Several common variables, such as presence of heavy vehicles, absence of lighting, and prevalence of mixed land use, were found to increase the probability of fatal pedestrian crashes in both cities.…”
Section: Prior Researchmentioning
confidence: 99%